FORMULASI DAN EVALUASI SEDIAAN CLAY MASK ESKTRAK ETANOL 96% DAUN SIRIH CINA (Peperomia pellucida L.) DENGAN VARIASI KAOLIN DAN BENTONITE. - M. Andi Chandra; Wahyudin Bin Jamaludin; Ariska Nurjannah Aman, A.N. (Jurnal Insan Farmasi Indonesia, 2025)
Peperomia pellucida L extract exhibits antibacterial activity and may be developed into a cosmetic clay mask. Variations in kaolin and bentonite concentrations can affect the physical properties and stability of the formulation. This study aimed to evaluate the characteristics of clay mask formulations containing ethanol extract from Chinese betel leaf and to identify the most optimal formulation based on stability testing via the cycling test method. An experimental method was used with six variations of kaolin and bentonite: F1 (30% kaolin; 20% bentonite), F2 (32.5%; 17.5%), F3 (35%; 15%), F4 (37.5%; 12.5%), F5 (0%; 25%), and F6 (40%; 0%). Evaluations included organoleptic properties, homogeneity, pH (4.76–5.12), spreadability (4.05–4.37 cm), moisture content (33.3–38.01%), drying time (16–30 minutes), and viscosity (3,600–16,833 mPa·s). The results showed that all formulations exhibited good physical characteristics. Formulation F4 (37.5% kaolin and 12.5% bentonite) was the optimal formulation based on its superior stability, appropriate drying time, viscosity within the ideal range, and skin- compatible pH.